Influence of Economy, Energy, and Population on Foreign Direct Investment and CO2 Emissions in ASEAN-5 Countries - Susilawati, Susilawati; Satrianto, Alpon (International Journal of Energy Economics and Policy, 2024)
This research aims to examine foreign direct investment and carbon dioxide (CO2) emissions in ASEAN-5 countries, including Indonesia, Malaysia, the Philippines, Singapore and Thailand during the 2000-2020 period. The analytical method used is simultaneous equation analysis. The results of the foreign direct investment simultaneous equation research show that CO2 emissions, economic growth, international trade, and renewable energy consumption simultaneously have a significant effect on foreign direct investment in ASEAN-5 countries. Partially, CO2 emissions have a significant and negative effect on foreign direct investment. International trade has a significant and positive effect on foreign direct investment. Meanwhile, economic growth and renewable energy consumption have no effect on foreign direct investment. Furthermore, the results of the simultaneous equation analysis of CO2 emissions show that foreign direct investment, renewable energy consumption, population, and energy intensity simultaneously have a significant effect on CO2 emissions in ASEAN-5 countries. Partially, foreign direct investment, population, and energy intensity have a significant and positive effect on CO2 emissions, while renewable energy consumption has a significant and negative effect on CO2 emissions in ASEAN-5 countries.